2017
DOI: 10.1097/ajp.0000000000000496
|View full text |Cite
|
Sign up to set email alerts
|

Common Pediatric Pain Disorders and Their Clinical Associations

Abstract: In light of their extensive associations, the common pain conditions, persistent pain, restless legs syndrome, iron deficiency, anxiety and depression, are likely to involve common etiological mechanisms that warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 83 publications
1
21
0
Order By: Relevance
“…While the relationship between pain problems and medical conditions remains a central question, population‐based studies of child/adolescent pain generally indicate that only a small proportion of chronic pain can be attributed to identified medical conditions (King et al, 2011). Clinicians and epidemiologists alike (Donnelly et al, 2017; Schechter, 2014; Williams, Spector, & MacGregor, 2010), often conceptualize adolescent pain proclivity as a unitary phenomenon that manifests via multiple pain problems across different anatomical sites. However, no study has yet documented how multiple adolescent pain problems aggregate into distinct temporal trajectories, and how these trajectories are shaped.…”
Section: Introductionmentioning
confidence: 99%
“…While the relationship between pain problems and medical conditions remains a central question, population‐based studies of child/adolescent pain generally indicate that only a small proportion of chronic pain can be attributed to identified medical conditions (King et al, 2011). Clinicians and epidemiologists alike (Donnelly et al, 2017; Schechter, 2014; Williams, Spector, & MacGregor, 2010), often conceptualize adolescent pain proclivity as a unitary phenomenon that manifests via multiple pain problems across different anatomical sites. However, no study has yet documented how multiple adolescent pain problems aggregate into distinct temporal trajectories, and how these trajectories are shaped.…”
Section: Introductionmentioning
confidence: 99%
“…Prompted by publications in which concern was expressed about inadequate differentiation between the two phenotypes, 10‐12 and by our finding that children diagnosed with GP had a three‐fold increase in periodic limb movements of sleep, 9 we added an exclusion clause, urge to move the legs (associated with lower limb pain), the key symptom of RLS, resulting in a subset termed GP‐Specific. When compared with GP, GP‐Specific was shown to be a purer phenotype, retaining the indications of genetic influence while losing those associations which relate to RLS, iron deficiency, and recurrent abdominal pain 14 . This study provides preliminary evidence that Walters 11 was correct, there is a subpopulation of children with GP who have symptoms of RLS, necessarily RLS‐Painful 6,17,23 because lower limb pain has always been essential for the diagnosis of GP.…”
Section: Discussionmentioning
confidence: 74%
“…This study is a component of a larger twin family case–control study, association analyses having been reported by Donnelly et al 14 Families of twins aged 3–18 years were recruited via the database of Twins Research Australia Registry (TRA). 15 Further information about TRA can be found at: https://www.twins.org.au/research/twin‐and‐data‐resource/70membership .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LBP was recently identified as the third most frequent cause of paediatric pain disorders 15 among children and adolescents,withprevalence comparable to adults [16][17][18][19][20] .However, although FRP hasbeen extensively studied in adults with LBP, there is a lack of electromyography (EMG) data on children and adolescents with LBP 21 . To the best of our knowledge, only one study has evaluated FRP in adolescents during a slumped sitting task 22 .It reported that 14-16 years old adolescents suffering non-specific chronic LBP (NSCLBP)showed a significant reduction in the activity of their thoracic erector spinae muscles during slumped sitting in comparison with usual sitting, suggesting the presence of anFRP.…”
Section: Introductionmentioning
confidence: 99%